2018
DOI: 10.1172/jci.insight.98522
|View full text |Cite
|
Sign up to set email alerts
|

NRG1-Fc improves metabolic health via dual hepatic and central action

Abstract: Neuregulins (NRGs) are emerging as an important family of signaling ligands that regulate glucose and lipid homeostasis. NRG1 lowers blood glucose levels in obese mice, whereas the brown fat-enriched secreted factor NRG4 protects mice from high-fat diet-induced insulin resistance and hepatic steatosis. However, the therapeutic potential of NRGs remains elusive, given the poor plasma half-life of the native ligands. Here, we engineered a fusion protein using human NRG1 and the Fc domain of human IgG1 (NRG1-Fc) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 38 publications
3
54
0
Order By: Relevance
“…While circulating NRG1 has previously been shown to act directly on the central nervous system [22,55] , liver [36,55] , skeletal muscle [56] , and cardiac muscle [24] here we propose an additional site of action within adipose tissues. We present a model that Type III NRG1 is epigenetically regulated and endogenously produced within adipose as a molecular rheostat controlling adipose expandability.…”
Section: Discussionmentioning
confidence: 64%
“…While circulating NRG1 has previously been shown to act directly on the central nervous system [22,55] , liver [36,55] , skeletal muscle [56] , and cardiac muscle [24] here we propose an additional site of action within adipose tissues. We present a model that Type III NRG1 is epigenetically regulated and endogenously produced within adipose as a molecular rheostat controlling adipose expandability.…”
Section: Discussionmentioning
confidence: 64%
“…EGF binds EGFR to induce lipogenesis in the liver, and increase TG secretion (Scheving et al, 2014). NRG1 acts on ErbB3 and/or ErbB4 to inhibit gluconeogenesis in the liver (Ennequin et al, 2015;Zhang et al, 2018), and to increase glucose uptake and oxidative phosphorylation in myotubes (Canto et al, 2004(Canto et al, , 2007Suárez et al, 2001). NRG1 also decrease food intake by acting on ErbB4 in the brain (Ennequin et al, 2015;Zhang et al, 2018).…”
Section: Epidermal Growth Factormentioning
confidence: 99%
“…Thus, global deletion of NRG1 results in embryonic lethality, while knockouts of NRG2-4 develop normally (Meyer and Birchmeier, 1995;Britto et al, 2004;Hayes et al, 2016). More recently, several lines of evidence point to a role of NRGs in the control of metabolism via actions on muscle, liver, adipose tissue and the hypothalamus Zhang et al, 2018). The four NRG genes encode for several isoforms, most of which contain a transmembrane domain and an N-terminal extracellular EGF-like domain (Burden and Yarden, 1997).…”
Section: The Neuregulinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nrg4 acts via paracrine, autocrine or endocrine mechanisms by releasing the epidermal growth factor (EGF)-like domain after photolytic cleavage [3,4]. Numerous studies showed that decreased Nrg4 levels were closely associated with obesity, insulin resistance, diabetes mellitus, dyslipidemia, metabolic syndrome, non-alcoholic fatty liver disease, inflammation, oxidative stress, and macrovascular disease such as coronary artery disease, myocardial infarcts, subclinical cardiovascular disease (CVD) in rodents and humans [3,[5][6][7][8][9][10][11][12][13][14][15], while all above factors have been reported to contribute to the development of DNP [1-3, 16, 17], suggesting indirectly that Nrg4 appears to play a crucial role in the development of DNP.…”
mentioning
confidence: 99%